The Cuntz semigroup as an invariant for C-algebras - Coward, Kristofer T.; Elliott, George A.; Ivanescu, Cristian (My University, 2008)
A category is described to which the Cuntz semigroup belongs and as a functor into which it preserves inductive limits.
Keywords: Cuntz semigroup